Trauma and suicidality in adolescents with substance use disorders - Mira Vasileva; Sören Kuitunen-Paul; Veit Roessner; Evgenii Shvedovskii; Vera Clemens; Jörg M. Fegert; Yulia Golub (Child and Adolescent Psychiatry and Mental Health, 2026)
Abstract Background Substance use and traumatic experiences have been identified as risk factors for suicidal ideation and behavior in community samples. The aim of this study was to explore these associations in a clinical sample of adolescents with substance use disorder (SUD). Methods The sample included N = 342 adolescents aged 12 to 19 years from a specialized SUD outpatient unit. They reported on their substance use, trauma history, symptoms of posttraumatic stress disorder (PTSD) and depression, and life satisfaction either in a structured clinical interview or standardized questionnaires; they also completed a task assessing inhibitory control. These variables were compared for adolescents with and without suicidal ideation or behavior. Classification and Regression Trees (CART) models were developed to describe subgroups of participants. Findings Overall, 34.2% of adolescent SUD outpatients reported suicidal ideation in the last two weeks and 26.0% fulfilled the criteria for suicidal behavior disorder in the last two years according to DSM-5. Female gender (OR = 2.88 and OR = 4.30) and sexual abuse (OR = 4.55 and OR = 5.33) were associated with higher odds of both suicidal ideation and behavior, respectively. Adolescents with suicidal ideation or behavior had significantly more severe SUD-related problems ( d = -0.46 and d = -0.36), symptoms of PTSD ( d = -1.38 and d = -1.04) and of depression ( d = -1.77 and d = − 0.89) and lower life satisfaction ( d = 0.98 and d = 0.81). The CART models identified symptoms of depression and PTSD as the variables that best distinguished participant subgroups. Conclusions These results indicate high rates of suicidal ideation and behavior in adolescents with SUD and underline the importance of assessing trauma when identifying and preventing suicidality in this population.